Are purchase-triggered donations advantageous with competition?. Issue 3 (1st March 2017) - Chen, Li-Ming; Yang, Shu-Jung Sunny
Abstract: Introducing social responsibility in product development and promotional strategies can affect the cost and demand of a firm's product, as well as the social impact. We explore whether a firm should employ a purchase-triggered donations (PTD) strategy by proposing an analytical model in which a profit-maximizing firm decides on the product price and its donation amount to the society. Two dimensions of consumer behavior are considered – price and social concern. We identify two common forms of socially responsible action: profit-maximizing ethics, through which socially responsible behavior can actually improve firm profitability, and costly philanthropy, whereby firms engage in socially responsible behavior for their ethical and social values, even if their profitability is consequently reduced. We develop managerial insights by characterizing and exploring the optimal and equilibrium solutions. Contrary to conventional wisdom, our analysis shows that both monopolistic and duopolistic firms prefer not to engage in socially responsible behavior through PTD. On the other hand, if an upper limit is applied on the PTD amount, then competing firms may find themselves in equilibrium with either profit-maximizing ethics or costly philanthropy. In this sense, we conclude that PTD-based corporate social responsibility behavior is best described as a competitive necessity for firms engaged in competition.